Psychological distress in patients listed for liver transplantation - Martins,Patrícia Duarte (2006)
PURPOSE: To assess the level of depression in patients listed for liver transplantation. METHODS: Sixty-four adult patients, listed for liver transplantation, were submitted to psychological evaluation, including assessment of depression by means of the Beck Depression Inventory. RESULTS: Twenty-two percent of the patients had mild/major depression. The group consisted mainly of male patients aged 47 on average, with a history of alcohol abuse and a Meld (Model for End-Liver Disease) value of 14.5. Patients that had been awaiting liver transplant longer presented less severe liver disease according to the Child-Pugh criteria. CONCLUSION: It is extremely important to assess psychological distress in patients listed for liver transplantation. An interdisciplinary approach is essential to improve the patients' quality of life both in the pre- and post-transplant periods.